Effects of Triiodothyronine on Human Osteoblast-Like Cells: Novel Insights From a Global Transcriptome Analysis - Rodrigues, Bruna Moretto; Mathias, Lucas Solla; Deprá, Igor de Carvalho; Cury, Sarah Santiloni; de Oliveira, Miriane; Olimpio, Regiane Marques Castro; De Sibio, Maria Teresa; Gonçalves, Bianca Mariani; Nogueira, Célia Regina (Frontiers in Cell and Developmental Biology, 2022)
BACKGROUND: Thyroid hormones play a significant role in bone development and maintenance, with triiodothyronine (T3) particularly being an important modulator of osteoblast differentiation, proliferation, and maintenance. However, details of the biological processes (BPs) and molecular pathways affected by T3 in osteoblasts remain unclear. METHODS: To address this issue, primary cultures of human adipose-derived mesenchymal stem cells were subjected to our previously established osteoinduction protocol, and the resultant osteoblast-like cells were treated with 1nM or 10nM T3 for 72h. RNA sequencing (RNA-Seq) was performed using Illumina platform, and differentially expressed genes (DEGs) were identified from the raw data using Kallisto and DESeq2. Enrichment analysis of DEGs was performed against the Gene Ontology Consortium database for BP terms using the R package clusterProfiler and protein network analysis by STRING. RESULTS: Approximately 16,300 genes were analyzed by RNA-Seq, with 343 DEGs regulated in the 1nM T3 group and 467 upregulated in the 10nM T3 group. Several independent BP terms related to bone metabolism were significantly enriched, with a number of genes shared among them (FGFR2, WNT5A, WNT3, ROR2, VEGFA, FBLN1, S1PR1, PRKCZ, TGFB3, and OSR1 for 1nM T3; and FZD1, SMAD6, NOG, NEO1, and ENG for 10nM T3). An osteoblast-related search in the literature regarding this set of genes suggests that both T3 doses are unfavorable for osteoblast development, mainly hindering BMP and canonical and non-canonical WNT signaling. CONCLUSIONS: Therefore, this study provides new directions toward the elucidation of the mechanisms of T3 action on osteoblast metabolism, with potential future implications for the treatment of endocrine-related bone pathologies.